Redaksi dan Daftar Isi, Jurnal Arsitekta Vol. 02 No. 02, November 2020 (Arsitekta : Jurnal Arsitektur dan Kota Berkelanjutan, 2020)
Redaksi dan Daftar Isi, Jurnal Arsitekta Vol. 02 No. 02, November 2020